'When the eye begins to see and the ear begins to hear': Teaching infant observation at university level. Issue 1 (3rd May 2020) - Abrahamsen, Gerd Randi
ABSTRACT: This paper presents the author's work in introducing a modified version of infant observation as a requirement of a university course in Early Childhood Education, a qualification course for Nursery Teachers in a Norwegian University. The author explores her psychoanalytic ideas about how learning takes place after tracing the paradigm shift in Early Years Education in a north European country in the late 20th and early 21st centuries. The author herself learnt a great deal about the Tavistock model of observation and in later work at the Tavistock Clinic. She emphasises the emotional component in learning, the nature of learning from a psychoanalytic perspective and on the countertransference (what is felt) along with what is seen and heard in observing young children. The expansion of nursery places in the author's country for three to six-year-old children led to an expansion in nursery teaching courses at universities and the opportunity to include 'learning form experience', along with other forms of learning, was taken. The paper also includes responses from questionnaires given to former students who had undertaken observations and their thoughts on its impact on their approach to their teaching work.